Pengaruh Fasilitas Belajar terhadap Prestasi Belajar Siswa Mata Pelajaran IPS - Ani Sapriani; Supriyadi (Arden Jaya Publisher, 2022)
Learning facilities are one of the factors that affect learning achievement. The purpose of this study is to reveal learning facilities (X) learning achievement (Y). This research is a quantitative research with a survey approach. The research sample used random sampling technique. The number of research samples was 52 students. Data collection using valid and reliable instruments. Analysis using simple regression, the results of this study reveal: (1) Linear Regression Equation Y = 66.493 + 0.146 X. (2) Learning facilities have a positive effect on learning achievement in Social Studies (Economics) class X SMK students. (3) Test the significance of the regression line equation Fhit 0.571 and p-value = 0.453 > 0.05, thus the Y or X regression is significant or the effect of facilities on student achievement in social studies subjects. (4) The correlation coefficient (rxy) = 0.106 and Fhit (Fchange) = 0.571, with p-value = 0.453 > 0.05. Thus the correlation coefficient of X and Y which means Significant.